Ultrastructural features of blood cells in HIF-1α gene variations in specialists of extreme conditions - Moiseyenko, E. V.; Rozova, K. V. (Journal of Education, Health and Sport, 2020)
The peculiarities of changes in the ultrastructure of blood cells due to personalized variations of the HIF-1α gene under hypoxic loading (breathing by gas mixture with reduced oxygen content up to 12% and achieving hypoxic state during heavy physical training on bicycle ergometer) were conducted. It was shown that allelic polymorphism of the HIF-1α gene influence on hypoxic-induced changes in the ultrastructure (and therefore function) of blood cells - the C / C genotype of winterers indicates their greater adaptive capacity compared to the C / T genotype that lies in the increasing the number of δ-granules in platelets, and reducing the number of α-granules and tubules of the inner skeleton. Such changes primarily indicate an increase in serotonin depot and therefore, indirectly, an increase in the contractile activity of the vascular wall, which may serve as a marker of the formation of adaptive reaction in response to hypoxic effects and stress. This is also indicated by the moderate swelling of mitochondria with an increase in their average diameter by 31%, which is considered to be a sign of an increase in the energy capacity of the mitochondrial apparatus in order to replenish ADP and ATP reserves for the further inclusion of adaptive responses. Hypoxic loading in winterers with C / T-genotype led to overstressing of platelet function with decrease in contractile activity of the vascular wall. The number of mitochondria in leukocytes significantly increased (by 24%) in winterers with C / C genotype; not only mitochondrial morphogenesis was activated, but also dynamic processes, in particular the association of organelles with pronounced longitudinal association and / or the formation of bridges between mitochondria. These facts are considered as an indicator of information exchange in the cell mitochondrial apparatus. In leukocytes of winterers with C / T genotype, changes in the mitochondrial apparatus were of a different nature: there were clear signs of hypoxic damage of organelles and the total percentage of structurally altered mitochondria exceeded 21%.